А) 3х-(9х-3)=3(4-2х)       б) (х^2 + 16)(/х/-6)(х^2-4х)   в)(1-2х):3 - (х+3):4=(2-4х):5 г) /6/3+2/+4/-8=32

А) 3х-(9х-3)=3(4-2х)       б) (х^2 + 16)(/х/-6)(х^2-4х)   в)(1-2х):3 - (х+3):4=(2-4х):5 г) /6/3+2/+4/-8=32
Гость
Ответ(ы) на вопрос:
Гость
а) 3х-(9х-3)=3(4-2х)      3x-9x+3=12-6x       0=9 – нет решений   б) (х^2 + 16)(/х/-6)(х^2-4х)     непонятно (х^2-4х) – в числителе или знаменателе     в)(1-2х):3 - (х+3):4=(2-4х):5     20*(1-2x)-15*(x+3)=12*(2-4x)     20-40x-15x-45=24-48x     7x=-49     x=-7   г) /6/3+2/+4/-8=32     непонятная запись!
Не нашли ответ?
Ответить на вопрос
Похожие вопросы